Utilizing Canva Platform to Improve Students’ Achievement in English Learning and Teaching - Maria, Bernadin; Februati, Noenoek; Yuliatin, Umi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The issue that this research focuses was the students’ low achievement in learning English. This followed the condition where the students showed their unpreparedness in attending the English learning and teaching program. To address this problem, the effort to improve the students’ achievement was made by utilizing Canva platform to redesign the present English for Specific Purposes material. This research, therefore, was conducted with the aim of determining whether the students improved their achievement when they used the English learning and teaching material designed with Canva platform. To prove the existence of such improvement, the data was collected from the same group of research subjects consisting of 76 students of Polytechnic of Energy and Mineral through the pre-test and post-test. Both data was, then, compared and the result of the comparison was t = 4.22 which equaled to p-value= 0.000. Since the significance level α = 0.05, it could be said that Null Hypothesis / H0, there was no improvement of the students’ achievement when they used Canva-based designed material, was rejected because p-value α. It meant that the Alternative Hypothesis / H1, there was an improvement of the students’ achievement when they used Canva-based designed material, was accepted